Microvascular basal lamina damage after embolic stroke in the rat: relationship to cerebral blood flow - Hamann, Gerhard; Schröck, Helmut; Burggraf, Dorothe; Wunderlich, Nathalie; Liebetrau, Martin; Kuschinsky, Wolfgang (Journal of cerebral blood flow & metabolism, 2003)
Microvascular basal lamina damage has been demonstrated after balloon occlusion of the middle cerebral artery in the nonhuman primate and after intravascular filament occlusion in the rat. The aim of the present study was to investigate in the rat whether microvascular damage can be found in the stroke model of intracarotid clot injection as early as 3 hours after clot injection and whether microvascular damage relates to the level of regional cerebral blood flow (rCBF). Microvascular densities and total stained microvascular areas were determined by immunohistochemistry of collagen type IV in cortex and basal ganglia and automatic video-imaging analysis. rCBF was measured by autoradiography in the same brain areas. Compared with the corresponding areas in the nonischemic hemisphere, a significant loss of microvascular density (−16%) and total stained microvascular areas (−10%) was observed in these areas. The reduction of microvascular basal lamina staining was comparable in all animals and was not related to the value of rCBF when measured 3 hours after onset of embolic stroke. In conclusion, microvascular damage occurs as soon as 3 hours after intracarotid clot injection, even in brain areas in which rCBF has returned to normal values.
First published November 1, 2003
Gesehen am 05.05.2021